Thompsonella nellydiegoae (Crassulaceae ), una nueva especie del sur de México - Carrillo-Reyes, Pablo; Pérez-Calix, Emmanuel (Instituto de Ecología, A.C., 2008)
Based on collections made in the Mexican states of Guerrero, Oaxaca and Puebla, Thompsonella nellydiegoae is described as new species and illustrated. It is compared with Thompsonella platyphylla Rose, which seems to be the closest related species and can be distinguished by its large inflorescences up to 1 m high, with compact cincinni of up to 10 flowers and by having leaves with red and crenulate margins. It is also compared with T. colliculosa Moran and T. garcia-mendozae P. Carrillo et Pérez-Calix, with which it shares some morphological features.